Development of Jute Braided Sapling Bag for Nursery Use. Issue 2 (3rd March 2016) - Ghosh, Mahuya; Biswas, Debkumar; Sanyal, Partha
Abstract : A tri-axial braided construction was chosen to develop nursery sapling bag, an agrotextile, from jute by employing a novel process. This product is meant as an eco-friendly substitute of plastic-based nursery sapling polybags which are very commonly used in horticultural or forest nurseries for raising plant seedlings. To develop a cost-effective product with high cover and low mass, the scope of standard jute yarns (fine and coarse both) and 'jute tape' was explored as 'axial material' during braiding. Jute tape was found to be effective in providing better cover and lower mass in the product. Jute tape-based sapling bag developed was found to be superior to polybags in respect of soil loss during handling in nursery. Furthermore, soil-analysis experimentation revealed that biodegraded jute bag enhanced soil nutrient level considerably with organic carbon, potassium, and phosphorus.